2020
DOI: 10.1007/s00540-020-02791-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous basal infusion versus programmed intermittent bolus for quadratus lumborum block after laparoscopic colorectal surgery: a randomized-controlled, double-blind study

Abstract: Background Quadratus lumborum block (QLB) has recently attracted attention as a part of multimodal analgesia after abdominal surgery. It has been shown that programmed intermittent boluses of local anesthetic can produce better analgesia and wider sensory blockade compared with continuous basal infusion with some peripheral nerve blocks. The present study was conducted to see if this theory holds true for QLB in patients undergoing laparoscopic colorectal surgery. Methods Fifty patients undergoing laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…When comparing the QLB to TAP block, Deng et al 81 found opioid-sparing, and Huang et al 82 reported marginal analgesic and opioid-sparing effects in favour of QLB. Aoyama et al 83 found no difference in analgesic effect when QLB was performed as a continuous infusion versus programmed intermittent bolus infusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the QLB to TAP block, Deng et al 81 found opioid-sparing, and Huang et al 82 reported marginal analgesic and opioid-sparing effects in favour of QLB. Aoyama et al 83 found no difference in analgesic effect when QLB was performed as a continuous infusion versus programmed intermittent bolus infusion.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies had more than two relevant study arms. These were separately listed for each relevant comparison, making the sum of studies in the following listing higher than the number of studies included: seven studies investigating adjuvant systemic analgesics, 39–45 three studies investigating varying degrees of neuromuscular blockade, 46–48 seven studies investigating intravenous lidocaine, 43,49–54 six studies investigating epidural analgesia, 55–60 four studies investigating spinal opioids, 55,61–63 twenty-eight studies investigating truncal nerve blocks, 53,58–60,64–87 seven studies investigating wound infiltration, 54,57,72–74,88,89 four studies investigating intraperitoneal local anaesthetics (IPLA) 90–93 and seventeen studies investigating surgical techniques 94–110 . Supplemental Table 1, http://links.lww.com/EJA/A901 lists the summary of key results from studies evaluating systemic analgesics, systemic analgesic adjuncts, regional analgesia and surgical procedures used to support the recommended interventions in patients after laparoscopic colectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonging the analgesic duration of QLB is favorable for patients. Several studies (23)(24)(25) have shown that various adjuvants (such as dexmedetomidine, dexamethasone) or intravenous drugs (lidocaine, ketamine) used in conjunction with QLB can prolong the analgesic time of QLB, and the placement of catheters for sustained analgesia is also an option (26). However, the mechanisms behind them and their broad clinical applications still require further exploration in the future.…”
Section: B Amentioning
confidence: 99%